Why Don’t Voters Vote Based on Their Socioeconomic Status? A Spatial Model Analysis - 문우진 (한국정치학회보, 2018)
This paper presents a theory of socioeconomic status voting (SES voting) to explain why voters do not vote based on their SES. An analysis of a spatial model reveals that SES voting is in negative relationships with (1) voters' sensitivity to valences, (2) differences in parties' valences, (3) similarities in parties' redistribution policies, (4) voters' sensitivity to policies other than redistribution policies, (5) the polarization of the parties' positions over the non-redistributive policies, and (6) incomplete information about the parties policies and valences. Using these results, this paper explains why class voting is more salient in the United Kingdom than South Korea and the United States. Lastly, this paper discusses implications that the results of this paper have for representative democracy and income inequality.
Keywords: 사회경제적 지위투표; 공간이론; 사회균열; 대의민주주의; 소득불평등; SES voting; spatial model; social cleavages; representative democracy; income inequality